The clinical and genomic distinctions of Class1/2/3 BRAF-mutant colorectal cancer and differential prognoses - Yungchang Chen; Hao Sun; Yanhong Deng; Yutong Ma; He Huang; Yang Liu; Yaru Zhang; Hongyu Zhang; Sheng Ye; Mingyan E; Hongqiang Guo; Mengmeng Wu; et al. (BMC, 2023)
Abstract BRAF mutations are the oncogenic drivers in colorectal cancer and V600 mutations (Class1), which lead to RAS-independent active monomers, are the most common mutation types. BRAF non-V600 mutants can be further classified as RAS-independent active dimers (Class2) and RAS-dependent impaired kinase (Class3). We retrospectively reviewed the mutational profiles of 328 treatment-naïve colorectal tumors with BRAF mutations detected using capture-based hybrid next-generation sequencing targeting 400 + cancer-related genes. The clinical and genetic distinctions of patients harboring Class1/2/3 BRAF mutations were investigated, which revealed that tumors with Class1 BRAF mutations showed more unique genomic profiles than those with Class2/3 mutations. Also, by using an external dataset from cBioPortal, we demonstrated that patients with Class3 BRAF mutations had the best survival outcomes compared to the other two subgroups. These findings promoted the development of anti-BRAF strategies by distinguishing BRAF mutant subgroups.